The relationship between dental caries lesion status and quality of life in children aged 10-12 years at SDN 196 Sukarasa, Bandung City: Hubungan status lesi karies gigi dengan kualitas hidup pada anak usia 10-12 tahun di SDN 196 Sukarasa Kota Bandung - Mahendra, Rajiva Tama; Apri, Anie; Adyatmaka, Irene; Sembiring, Linda Sari; Monica, Grace; Abigayl, Ivana (Makassar Dental Journal, 2024)
Dental caries lesions in children can have a significant impact on quality of life. According to WHO, QoL is a perception that comes from individuals consisting of functional abilities, interaction in society, psychological health, physical health, and life satisfaction. The purpose of this study was to determine the relationship between dental caries lesion status and quality of life in children aged 10-12 years at SDN 196 Sukarasa, Bandung City. Analytic observational descriptive research, with a cross-sectional study de-sign. Hypothesis testing was carried out using the Spearman Rank test. The results showed a mean DMF-T index value of 0.3 with low caries status (100%). The mean value of the def-t index was 2.1 with low (68%), medium (19%), and high (13%) caries sta-tus. There is a relationship between dental caries lesion status and quality of life in children. Statistically the correlation between the two is significant because it has a probability value of 0.000 (Sig.<0.05). The lower the score of the child's dental caries lesion sta-tus, the better the child's quality of life. It is concluded that dental caries lesion status can affect children's quality of life.